Validation rules for blood smear revision after automated hematological testing using Mindray CAL‐8000. Issue 4 (6th October 2016) - Buoro, Sabrina; Mecca, Tommaso; Seghezzi, Michela; Manenti, Barbara; Azzarà, Giovanna; Ottomano, Cosimo; Lippi, Giuseppe
Abstract : Background: This article was aimed to test the use of validation rules for blood smear review after automated hematological testing using Mindray CAL‐8000 (two hematological analyzers and one autoslider). Methods: This study was based on 1013 peripheral blood samples (PB) referred for routine hematological testing. Results of testing on CAL‐8000 were analyzed using both locally derived and International Consensus Group for Hematology (ICGH) validation rules, and then compared with data obtained by optical microscopy (OM). A workflow analysis was also completed. Results: The overall agreement with locally derived and ICGH criteria was 91% and 85%, but a higher sensitivity was observed for locally derived criteria (0.97 vs 0.95). The percentage of false negative and false positive samples was 2.1% and 7.1% using ICGH criteria, and was 1.4% and 14% using locally defined rules. The throughput of CAL‐8000 system was 208 samples/h, with a percentage of OM analysis comprised between 14% and 17%, and sensitivity of 0.97. As regards personnel activity, we estimated 0.8 full‐time equivalent (FTE) of technical staff and 0.7 FTE of personnel for clinical validation of data and blood smear review. Conclusion: These results show that customization of validation rules is necessary for enhancing the quality of hematological testing and optimizing workflow.